1995
DOI: 10.5962/bhl.part.22804
|View full text |Cite
|
Sign up to set email alerts
|

Life histories of stoneflies (Plecoptera) in the Rio Conejos of southern Colorado

Abstract: Thirty-one stonefly species representing eight famihes were collected during the March 1987 to May 1990 study period. Genera represented by more than one species included Capnia. Utacapnia, Taenionema. Siiuallia, Triznaka, Isogenoides, and Isoperla. Peak species richness was recorded on or near the summer solstice in 1988 and 1989. Climatic differences between years were reflected in nymphal development and emergence phenology of most species. New or important corroborative life histoiy data are presented for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…Freilich (1991), who worked only with larvae with headcapsule widths of more than 3.0 mm, also reported a 3-year larval life in Pacific Creek, Wyoming. DeWalt and Stewart (1995) found a 9-to10-month egg stage and estimated a 38-month larval life, based on head-capsule widths, in the Rio Conejos, Colorado. Townsend and Pritchard (1999) showed that P. californica eggs from the Crowsnest River in southern Alberta took a minimum of 182 days (or >1790 day-degrees above the developmental zero (the intercept on the temperature axis of the linear regression of development rate on temperature)) for 50% hatch in the laboratory, with no observable development for approximately 80 d at any temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Freilich (1991), who worked only with larvae with headcapsule widths of more than 3.0 mm, also reported a 3-year larval life in Pacific Creek, Wyoming. DeWalt and Stewart (1995) found a 9-to10-month egg stage and estimated a 38-month larval life, based on head-capsule widths, in the Rio Conejos, Colorado. Townsend and Pritchard (1999) showed that P. californica eggs from the Crowsnest River in southern Alberta took a minimum of 182 days (or >1790 day-degrees above the developmental zero (the intercept on the temperature axis of the linear regression of development rate on temperature)) for 50% hatch in the laboratory, with no observable development for approximately 80 d at any temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In the Provo river, Utah, a four-year life cycle was estimated for P. californica (Branham and Hathaway 1975). DeWalt and Stewart (1995) also estimated a four-year life cycle in the Rio Conejos, Colorado. Given the variability in the duration of diapause reported by Pritchard and Townsend (2000) we predict that cohort splitting is common enough in P. californica to lead to little or no genetic differentiation among cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Most often, their emergence periods are synchronous and short, with different species emerging in temporal succession (Hynes, 1976;Zwick, 2011). Although many environmental factors influence emergence of aquatic insects, water temperature and photoperiod have been recognized as the most important for stonefly emergence (Hynes, 1976;Flannagan and Cobb, 1991;DeWalt and Stewart, 1995;Zwick, 2011;Ivković et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%